Webs of power : notes from the global uprising - Starhawk (New Society Publishers, 2002)
"Since her arrest and five-day jail stay during the Seattle anti-WTO protests in November 1999, Starhawk has poured her energy into the global justice movement, participating in direct actions, leading nonviolence training workshops, and writing, always writing. Webs of Power is the outcome: an account from the front lines of that movement as it migrated from Seattle to Prague, then Brazil, Quebec City, and Genoa. As well as reporting the actions on the street, it includes a privileged glimpse behind the scenes, too, at the fierce discussion of the issues, strategies, and tactics of an always-evolving social movement. The book is also a personal vision of what an alternative future might look and feel like beyond the version offered up to us by the promoters of corporate globalization. Webs of Power is a unique contribution to our understanding of one of the most pivotal struggles of our time."--Jacket